International Successions in Spain: The Impact of a New EU Regulation (Spanish Yearbook of International Law, 2011)
The arrangement of cross-border successions is a real challenge nowadays for both citizens and authorities due to the multicultural profile of today’s societies together with the current diversity of regulations, both at the substantive and conflicts levels. On 14 October 2009, the European Union adopted a new Proposal for a Regulation on international successions, a comprehensive instrument which will entail the harmonization within the EU of the conflicts regulation of cross-borders inheritances. The text finally adopted will necessarily have to provide an adequate equilibrium of the interests of people living in Europe to be successful. Material justice should not only focus on the European citizens’ expectations but also on immigrants’ needs, new neighbours who live in Europe and have their own expectations as to the planning of their successions. In the light of the solutions provided by the Proposal, it seems like this aim has been taken into consideration, although some concerns about the current drafting still remain. The present commentary aims at providing an overview of the main solutions of the Proposal, mainly focusing on the needs of multicultural societies like the one existing in Spain, where the regulation in force does not grant to reach the most suitable solutions to every case.